Effect of biochar modified with magnetite nanoparticles and HNO3 for efficient removal of Cr(VI) from contaminated water: A batch and column scale study. (June 2020) - Imran, Muhammad; Khan, Zia Ul Haq; Iqbal, Muhammad Mohsin; Iqbal, Jibran; Shah, Noor Samad; Munawar, Saba; Ali, Shafaqat; Murtaza, Behzad; Naeem, Muhammad Asif; Rizwan, Muhammad
Abstract: Chromium (Cr) poses serious consequences on human and animal health due to its potential carcinogenicity. The present study aims at preparing a novel biochar derived from Chenopodium quinoa crop residues (QBC), its activation with magnetite nanoparticles (QBC/MNPs) and strong acid HNO3 (QBC/Acid) to evaluate their batch and column scale potential to remove Cr (VI) from polluted water. The QBC, QBC/MNPs and QBC/Acid were characterized with SEM, FTIR, EDX, XRD as well as point of zero charge (PZC) to get an insight into their adsorption mechanism. The impact of different process parameters including dose of the adsorbent (1–4 g/L), contact time (0–180 min), initial concentration of Cr (25–200 mg/L) as well as solution pH (2–8) was evaluated on the Cr (VI) removal from contaminated water. The results revealed that QBC/MNPs proved more effective (73.35–93.62-%) for the Cr (VI) removal with 77.35 mg/g adsorption capacity as compared with QBC/Acid (55.85–79.8%) and QBC (48.85–75.28-%) when Cr concentration was changed from 200 to 25 mg/L. The isothermal experimental results follow the Freundlich adsorption model rather than Langmuir, Temkin and Dubinin-Radushkevich adsorption isotherm models. While kinetic adsorption results were well demonstrated by pseudo second order kinetic model. Column scale experiments conducted at steady state exhibited excellent retention of Cr (VI) by QBC, QBC/MNPs and QBC/Acid at 50 and 100 mg Cr/L. The results showed that this novel biochar (QBC) and its modified forms (QBC/Acid and QBC/MNPs) are applicable with excellent reusability and stability under acidic conditions for the practical treatment of Cr (VI) contaminated water. Graphical abstract: Image 1 Highlights: A novel biochar and its composites (QBC/MNPs and QBC/Acid) were used for Cr(VI) removal. Composites were characterized with FTIR, SEM, EDX, XRD and PZC. Experimental data were modelled with equilibrium and kinetic models. QBC/MNPs could effectively remove Cr(VI) with adsorption capacity of 77.35 mg/g. Column scale removal showed excellent retention of Cr and reusability. Abstract : Biochar (QBC/MNPs) was applicable with excellent reusability and stability under acidic conditions for the practical treatment of Cr (VI) contaminated water.